2021
DOI: 10.1007/s10198-021-01388-9
|View full text |Cite
|
Sign up to set email alerts
|

The residential healthcare for the elderly in Italy: some considerations for post-COVID-19 policies

Abstract: In Italy, the COVID-19 pandemic and the death of many elderly people have put in evidence the uneven territorial distribution of nursing homes, which have amplified the spread and severity of the pandemic. By applying a pooled OLS model to the Italian regions, over the 2010–18 period, we investigate the demand factors, market forces and institutional drivers of the spatial distribution of residential healthcare for the elderly. Using a fine-grained approach that considers specific regional and age-related elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…32 At the fourth wave, the NHs included reported from a few (9.9%) residents to almost all (91.6%) residents being infected, and in all, there was a higher mortality than that reported in other countries, 33 although data available should be considered with prudence given that only at the end of the pandemic will it be possible to definite the precise mortality rates according to the causes. 34,35 Our NHs were not prepared to cope with a pandemic, as reported in many facilities around the world. 26 Their marginal role in the health-care sector, with a poor coordination with hospitals considered to be at the core of the healthcare system, 7 might have rendered more challenging the interventions' identification 6 and implementation, along with the pre-existing frailty of the NH system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 At the fourth wave, the NHs included reported from a few (9.9%) residents to almost all (91.6%) residents being infected, and in all, there was a higher mortality than that reported in other countries, 33 although data available should be considered with prudence given that only at the end of the pandemic will it be possible to definite the precise mortality rates according to the causes. 34,35 Our NHs were not prepared to cope with a pandemic, as reported in many facilities around the world. 26 Their marginal role in the health-care sector, with a poor coordination with hospitals considered to be at the core of the healthcare system, 7 might have rendered more challenging the interventions' identification 6 and implementation, along with the pre-existing frailty of the NH system.…”
Section: Discussionmentioning
confidence: 99%
“… 32 At the fourth wave, the NHs included reported from a few (9.9%) residents to almost all (91.6%) residents being infected, and in all, there was a higher mortality than that reported in other countries, 33 although data available should be considered with prudence given that only at the end of the pandemic will it be possible to definite the precise mortality rates according to the causes. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that characteristics of the residents in long-term care facilities (age, higher body mass index, male sex, and renal impairment) had a different impact on the death rate as well as the quality level of healthcare and the adequacy of safety measures adopted to face the spread of the infection and its deadly consequences (specific training of the staff, good staff/resident ratio) [ 21 , 22 , 23 , 24 , 25 ]. In Italy, the territorial distribution of long-term care facilities (or residential care homes) exhibits a gradient moving from the North to the South of the country and has been considered significant in the distribution of death during the COVID-19 pandemic [ 26 ]. Concerns about the possibility that personnel represented the source of COVID-19 introduction and promoted the spread of the infection among the residents favored the onset of claims and triggered efforts to ensure equal access to high-quality healthcare across long-term care facilities as well as to provide the extensive vaccination of residents and personnel [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%